2021
DOI: 10.1371/journal.pone.0252274
|View full text |Cite
|
Sign up to set email alerts
|

Directly observed therapy at opioid substitution facilities using sofosbuvir/velpatasvir results in excellent SVR12 rates in PWIDs at high risk for non-adherence to DAA therapy

Abstract: Background & aims We evaluated the effectiveness of sofosbuvir/velpatasvir (SOF/VEL) in difficult-to-treat PWIDs with presumed high risk for non-adherence to antiviral therapy using an innovative concept involving their opioid agonist therapy (OAT) facility. Methods N = 221 patients (m/f: 168/53; median age: 44.7 years (IQR 16.9); HCV-genotype 3: 45.2%; cirrhosis: 33.9%) treated with SOF/VEL were included. PWIDs at high risk for non-adherence to DAA therapy (n = 122) received HCV treatment alongside OAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…Starting treatment quickly and in a more individualized way improved the retention in care of PWID [ 17 , 20 , 24 , 26 ]. In agreement with our findings, recent research conducted in Vienna on DAAs administration as DOT (given at OST facilities) in PWID showed excellent SVR12 rates (99%) in this difficult-to-treat population, similar to patients with expected high treatment compliance in a standard setting [ 27 ]. In our study, although the rate of DAAs therapy completion was lower among patients treated in hospital, when we consider the entire subset of subjects who completed treatment, we observed similarly high virological success rates regardless from treatment setting with no statistically significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…Starting treatment quickly and in a more individualized way improved the retention in care of PWID [ 17 , 20 , 24 , 26 ]. In agreement with our findings, recent research conducted in Vienna on DAAs administration as DOT (given at OST facilities) in PWID showed excellent SVR12 rates (99%) in this difficult-to-treat population, similar to patients with expected high treatment compliance in a standard setting [ 27 ]. In our study, although the rate of DAAs therapy completion was lower among patients treated in hospital, when we consider the entire subset of subjects who completed treatment, we observed similarly high virological success rates regardless from treatment setting with no statistically significant differences.…”
Section: Discussionsupporting
confidence: 92%
“…When patients who had been lost to follow-up were not considered, SVR rates were 98.1% pre-COVID and 96.9% during COVID, confirming high SVR rates to DAA therapy as reported in previous studies. 23,[36][37][38] A large proportion of patients included in this study were members of high-risk groups for poor adherence. [23][24][25] Interestingly, the rate of patients with significant liver fibrosis/advanced chronic liver disease (F2/3/4) was higher during-COVID (Figure 3) and the dura- important means for patients to get information on the formal requirements to get access to healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the HCV hotline, the numbers of in‐ and out‐going phone calls, text messages and voicemails were recorded on a daily basis. Patient characteristics including age, sex, HCV‐RNA, HCV genotype (GT), date of HCV diagnosis, transmission route, SVR, use of the HCV hotline, liver fibrosis stage, HIV coinfection, as well as risk factors for non‐adherence including intravenous drug use and alcohol abuse 23 , 24 , 25 were retrieved from the medical records. Intravenous drug use was defined as ongoing or recent intravenous use of drugs, while alcohol abuse was defined as documented ongoing daily consumption of at least 60 g of alcohol 26 , 27 at DAA treatment initiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the prevalence of non-obese NAFLD among the general population also shows a great variation between 25% or lower in some Asian countries and more than 50%, for example in Austria [5]. Recent analyses showed that the incidence of primary liver cancer as well as of cirrhosis has been increasing during the last years and, while ongoing strategies to meet the World Health Organization's goal of viral hepatitis elimination by 2030 are in place to reduce the current burden of viral hepatitisinduced liver disease, fatty liver disease is continuously gaining importance with regard to the development of progressive liver disease and its complications [1,2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%